Soil water erosion assessment in Morocco through modeling and fingerprinting applications: A review - Houda Lamane; Rachid Moussadek; Bouamar Baghdad; Latifa Mouhir; Hamza Briak; Meriem Laghlimi; Abdelmjid Zouahri (Heliyon, 2022)
During the last century, a great deal of effort has been directed toward determining soil erosion rates using various methods under a wide range of climatic conditions, soil types, land uses, topography, and among others. Therefore, to better understand soil erosion studies in Morocco, a country with diverse physiography and climatic variations we undertook an analysis of national data of several soil erosion modeling and fingerprinting. The approach used for this research is a review of scientific articles, conference papers and thesis on soil erosion, focusing more on categorization of the different soil erosion models and other methods applied. The results reveal very interesting information as follows: (i) the distribution and frequency level of modeling and fingerprinting applications; the focus was on the north of the country: (Rif 32.89%, High Atlas 32.89%, Occidental Meseta 18.43% and Middle Atlas 10.53%), (ii) The (R) USLE models remain the most widely used models (51,32%) in Morocco, (iii) The support practice factor was severely lacking across the country, (iv) the highest erosion rate is concentrated in the Atlas and Rif mountains; and (v) a positive relationship between erosion rate and geological features, slope, climate, land use and cover, plus other environmental characteristics, as well as measurement and modeling conditions, and a negative relationship with the study areas size and scale. Even though the overall results show a high degree of variability, which cannot be explained by this combination of factors, but is at a minimum partly related to the experimental conditions. This overview research and database are designed to assist in the future assessment of soil erosion and to help define priorities for soil erosion research by providing a state of art for future focused and comprehensive analyses to address this issue of soil erosion in Morocco.